Human interface with safety instrumented systems in the chemical, petrochemical, oil and gas industries - Silva, Elisio Carvalho (Revista Gestão da Produção Operações e Sistemas, 2014)
Industrial processes became safer with automation. However, when these systems fail, it can cause major accidents. Thus, it is fundamental for these systems to be installed and maintained to avoid failures that can be transformed into accidents. Random and systematic failures are failures of automation systems. The first are predictable, however the second are caused by human factors, hence, it is impossible to foresee them. Thus, it becomes necessary to have good human factor management to avoid these dangerous failures. This paper briefly discusses human errors and comes up with a management to avoid systematic failures, taking in consideration the types and behavior of the errors. Applying this management, it will reduce human errors and, therefore, systematic failures. These actions will enhance the safety of industrial processes. Keywords: Human errors. Automation. Safety. Management.